the preservation of wooden antiques at Ahmed Zabana Museum - study models- - mazouz, chayma (Journal of Social Sciences and Humanities, 2024)
The topic of our study on the preservation of wooden antiques is the Museum of Ahmed Zabana oran. At the beginning of the topic, we touched on wood as a unique organic material. Wood is one of the key materials that played a key role in human history. It helped researchers and archaeologists discover many civilizations. Wood is used in relative history. We have identified the various factors to which they are exposed and lead to their demise over time. Finally, we have come up with an assessment of the medium of preservation of these wooden objects by studying some samples. We have therefore proposed a series of methods and methods to be followed to preserve them.